KANDUNGAN ALUMINIUM DALAM KALENG BEKAS DAN PEMANFAATANNYA DALAM PEMBUATAN TAWAS - Manuntun Manurung; Irma Fitria Ayuningtyas (Jurnal Kimia (Journal of Chemistry), 2010)
This research was performed to analyze the aluminium content in several wasted cans. The analysis usedAAS at 309.3 nm. This method was chosen since its operation is relatively simple but capable of analyzing low metalcontents (less than 1 ppm). The aluminium content of wasted cans ranges from 1.41% up to 16.04%. The aluminiumwas used to make alum, with the percentage of yield of 77.04% up to 96.81%, depending on the type or cans. Inother words, one gram of wasted cans produced 0.2335 grams up to 2.6857 grams of alum. The produced alum wascapable of purifying water.